Modeling and Dynamic Performance Analysis of Hydraulic Top Drive Main Transmission System with Long Hydraulic Pipelines. (16th April 2022) - Shi, Yuanling; Zhang, Pingsong
Abstract : Hydraulic top drive is the main power component used to drive drilling tools rotating to drill a hole for drilling rigs. Its main transmission system was built with hydraulic power source and hydraulic actuators. During the drilling procession, the hydraulic top drive is mounted on a derrick, and moving along its vertical guide rails. The hydraulic power station is usually placed on the drilling platform or the ground. In that way, long pipelines are needed to connect the hydraulic pumps and hydraulic motors. Thus, the effects on the performance of hydraulic top drive should not be neglected. A mathematical model of hydraulic top drive main transmission with differential equation of hydraulic units and state space equation of hydraulic long pipelines was deduced in this research. A simulation model was built using the AMESim software. And field drilling test of the hydraulic top drive was carried out in Songliao Basin Drilling Project (SK-II) well site. To verify and modify the virtual model, a comparison analysis was performed by setting the parameters and load of the three methods at the same values. The result of comparison shows that the simulation results are very close to the theoretical results and field drilling test data. Thus, the dynamic characteristics could be analyzed by this simulation model. Dynamic characteristics of the hydraulic top drive with different length and various diameters of pipelines were studied. The simulation results demonstrate that pipeline lengths and pipeline diameters affect the system in different laws, and it needs to comprehensively consider the system response speed, overshoot, and steady-state characteristics when choosing the size of pipelines for hydraulic top drive.